Molecular geometry from molecular tensegrity: a case study of gas-phase MX2 compounds - Ganguly, Parthasarathy (Current Science, 2006)
We define a tensegrity factor, t(00)(+/-), for X-M-X linkages of gas-phase MXn compounds (X is an atom of an insulating element) that is a measure of the matching of `ideal' 1,2-(single-bonded) M-X distance, d(MX)(00), to the `ideal' (non-bonded) 1,3-X–-X distances, d(MX)(00). The actually observed 1,3-distance, d(XX) is given (within 1% error) by 2CR(X)/F-S, where F-S (= 2-1.41(00)(+/-)) is shown to be an ab initio quantity with no adjustable parameter, no dependence on actual M-X distance or bond order and with 2CR(X) depending only on whether M is an atom of an insulating element (2CR(X) =d(XX)(00)) or whether M is metallic (2CR(X) = 1.1d(XX)(00)). This is illustrated for gas-phase MX2 compounds.
Keywords: gas-phase; molecular geometry; MX2 compounds; tensegrity

Molecular tensegrity: predicting 1,3-X–-X distance in gas-phase MXn (n <= 4) compounds from atomic sizes - Ganguly, Parthasarathy (Current Science, 2006)
This article extends an earlier definition(1) and use of molecular tensegrity for obtaining quantitatively the 1,3-non-bonded distances in gas-phase MX2 compounds to nearly 160 gas-phase MXn (n <= 4) inorganic compounds (including those of transition metal elements), once a transferable `core' atomic size is specified. The simple principles behind this methodology (involving only linear equations), its quantitative character, its transparency, its portability and its generality account very simply for molecular geometry in such compounds without requiring earlier theoretical methodologies. We also establish clear distinction in the prescription for obtaining the 1,3-distance when M is an atom of a metallic or insulating element.
Keywords: Atomic size; gas phase; molecular tensegrity; non-bonded distance